Morphological changes in venous walls caused by microfoam sclerotic surgery of varicosity - I. V. Irkin; V. A. Hodos; V. I. Zaritskaya (Patologìâ)
The work presents results of morphological studies of venous walls affected by the sclerosing microfoam which was reproduced out of different concentrations (2%, 3%, 5%) of sclerosing fluid. The data obtained allows to determine that the 3% sclerosing fluid concentration is the optimal, insofar the goal is to create favorable conditions for a high-quality fibrous vein transformation and at the same time to minimize eventual complications after a microfoam phlebosclerotic obliteration.